Saving God: Religion after Idolatry - Johnston, Mark (Princeton University Press, 2009)
In this book, Mark Johnston argues that God needs to be saved not only from the distortions of the "undergraduate atheists" (Richard Dawkins, Christopher Hitchens, and Sam Harris) but, more importantly, from the idolatrous tendencies of religion itself. Each monotheistic religion has its characteristic ways of domesticating True Divinity, of taming God's demands so that they do not radically threaten our self-love and false righteousness. Turning the monotheistic critique of idolatry on the monotheisms themselves, Johnston shows that much in these traditions must be condemned as false and spi